2019
DOI: 10.1111/cen.13946
|View full text |Cite
|
Sign up to set email alerts
|

Serum polyamine metabolic profile in autoimmune thyroid disease patients

Abstract: Summary Objective Polyamines are indispensable polycations and play important physiological roles in living cells. Some polyamine metabolites have been associated with autoimmune disorders. The aims of this study were to profile polyamine metabolites in autoimmune thyroid disease (AITD) and predict whether polyamine metabolites are associated with thyroid hormone, thyroid autoantibodies or disease progression. Design, patients and measurements A total of 136 participants were recruited, including Graves’ disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 34 publications
0
22
1
Order By: Relevance
“…We observed higher mean Spermidine serum levels in both controls and AD group compared to the values reported by other investigators for < 65-year-old healthy control subjects with normal body mass index (18-36 ng/ml) [15]. The discrepancy may have been resulted from differences in the method of measurement, since we used ELISA, whereas mass spectrometry was used in the other study.…”
Section: Discussioncontrasting
confidence: 77%
“…We observed higher mean Spermidine serum levels in both controls and AD group compared to the values reported by other investigators for < 65-year-old healthy control subjects with normal body mass index (18-36 ng/ml) [15]. The discrepancy may have been resulted from differences in the method of measurement, since we used ELISA, whereas mass spectrometry was used in the other study.…”
Section: Discussioncontrasting
confidence: 77%
“…Metabolomics performed were described in a previous study ( 14 ). In brief, LC-MS/MS analyses were performed using a 1290 UHPLC system (Agilent Technologies, Santa Clara, CA, USA) with a UPLC BEH Amide column (1.7μm, 2.1*100mm, Waters) coupled to Triple time-of-flight 6600 (Q-TOF, AB Sciex, Framingham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In smaller studies, metabolomics has been designed to investigate the underlying mechanisms and progression of certain diseases, or to reveal the potential roles of dietary and environmental exposures, as well as gut flora activity in chronic diseases ( 11 , 12 ). Multiple studies on metabolomic changes in GD adult patients have been reported, which showed that acylcarnitine and polyamine profiles were different between GD patients and healthy controls ( 13 , 14 ). Metabolic pathways, such as arginine and proline metabolism and aminoacyl-transfer ribonucleic acid (tRNA) biosynthesis have also been altered in GD patients ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics is a global and comprehensive analysis approach that identifies endogenous small molecule metabolites, which provide an explanation of the pathophysiology and metabolic changes in some diseases. In recent years, metabolomic analysis has been used to evaluate the metabolic differences of thyroid diseases (3)(4)(5)(6). However, recent studies showed some inconsistent to analyze each amino acid or bile acid extract and the diluted standards.…”
Section: Introductionmentioning
confidence: 99%